2016
DOI: 10.4236/jcpt.2016.61001
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Type Iof Azilsartan Polymorphs: Preparation and Analysis

Abstract: Azilsartan (2-ethoxy-1-([2'-(5-oxo-4,5-dihydro-1,2,4-oxadiazol-3-yl)biphenyl-4-yl]methyl)-1H-benzimidazole-7-carboxylic acid) is a new angiotensin II receptor antagonist used in the treatment of hypertension. This paper describes the preparation of type I crystal and its single crystal diffraction data, the comparison of the powder diffraction data for both type I and II crystals as well as their stability and solubility in methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…The particle size and crystal form of a drug also affect pharmacological efficacy, due to their ability to alter the physicochemical properties of solubility, dissolution, and dosage forms. During the crystallization of a drug, different crystal structures can be formed, as the packing of molecules in space change at different temperatures, solutions, and pressures [14][15][16][17]. Generally, the appearance, melting point, dissolution, and other aspects of the same drug are significantly different in diverse crystal forms, which correspondingly affect clinical efficacy [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The particle size and crystal form of a drug also affect pharmacological efficacy, due to their ability to alter the physicochemical properties of solubility, dissolution, and dosage forms. During the crystallization of a drug, different crystal structures can be formed, as the packing of molecules in space change at different temperatures, solutions, and pressures [14][15][16][17]. Generally, the appearance, melting point, dissolution, and other aspects of the same drug are significantly different in diverse crystal forms, which correspondingly affect clinical efficacy [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that there are four kinds of crystalline forms of this chemical, and the crystal form, size distribution, and polymorphism could influence its pharmaceutical quality and effectiveness . Despite sufficient studies on its polymorph, the solubility information of this drug has been ignored. Indeed, multiple solvents were applied in its crystallization and recrystallization process such as isopropanol, dimethylformamide, methanol, and acetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the stable polymorph is type I (P2 1 /C, Z = 4; a = 9.659 Å, b = 11.329 Å, c = 20.046 Å; β = 90.30°). 3 Because of the poor solubility of type I azilsartan crystals in water, improvement of the dissolution property is a major challenge to overcoming unsatisfactory drug efficacy. In general, the surface area of drug particles plays a role in determining their dissolution rate when wetted by luminal fluids, and therefore, reduction of their crystal size may be an effective way to dissolve the problem.…”
Section: Introductionmentioning
confidence: 99%